Single-incision laparoscopic rectopexy (Wells) with simultaneous sigmoidectomy in a case of complete rectal prolapse and a sigmoid tumor: report of a case - Miyo, Masaaki; Takemasa, Ichiro; Mokutani, Yukako; Uemura, Mamoru; Nishimura, Junichi; Hata, Taishi; Mizushima, Tsunekazu; Yamamoto, Hirofumi; Doki, Yuichiro; Mori, Masaki (Surgery today (Tokyo, Japan), 2015)
Recently, the technique of single-incision laparoscopic surgery for colorectal disease has rapidly disseminated in association with improvements in instrumentation and procedures, offering a less invasive procedure and excellent cosmetic results. We herein present the case of a 74-year-old female who suffered complete rectal prolapse with a pedunculated polyp (20 mm) in the sigmoid colon; the stalk of the polyp was too thick to perform endoscopic mucosal resection, which is associated with a high risk of bleeding. The patient was successfully managed using single-incision laparoscopic rectopexy (Wells) with simultaneous sigmoidectomy, a procedure that has not been reported in the literature to date. There were no perioperative complications. The patient’s constipation caused by the rectal prolapse improved, and no recurrence was observed for 2 months after the operation. This case emphasizes that complete rectal prolapse is a benign disease occurring in elderly patients that is well suited to treatment with minimally invasive single-incision laparoscopic surgery.